Edwards SAPIEN™ and Edwards SAPIEN XT™ transcatheter heart valves for the treatment of severe aortic stenosis. (November 2012) - Freeman, Melanie; Webb, John G
Aortic stenosis is the most common heart valve lesion, with aortic valve replacement being the most common type of valve surgery in the Western world. With the aging population, more and more patients are declined for surgical aortic valve replacement owing to age and comorbidities. Without intervention, morbidity is significant and early mortality inevitable. Transcatheter aortic valve replacement is an exciting technology offering an alternative, less invasive treatment in those not eligible for surgery. The Edwards SAPIEN™ and Edwards SAPIEN XT™ transcatheter heart valves are currently in widespread use, with promising outcomes in terms of short-to-medium-term mortality and valve durability in high-risk patients or patients not eligible for surgical valve replacement. Randomized trials are currently underway to assess transcatheter aortic valve replacement in lower risk surgical candidates, while long-term mortality data are keenly awaited.